The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ph14080717
|View full text |Cite
|
Sign up to set email alerts
|

Current Therapies in Clinical Trials of Parkinson’s Disease: A 2021 Update

Abstract: Parkinson’s disease (PD) is a progressive neurodegenerative disorder that currently has no cure, but treatments are available to improve PD symptoms and maintain quality of life. In 2020, about 10 million people worldwide were living with PD. In 1970, the United States Food and Drug Administration approved the drug levodopa as a dopamine replacement to manage PD motor symptoms; levodopa-carbidopa combination became commercialized in 1975. After over 50 years of use, levodopa is still the gold standard for PD t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 146 publications
0
57
0
Order By: Relevance
“…Yet, CNS drug developers practice their craft by adhering to two conflicting beliefs: (a) drugs for CNS disease can be developed, and (b) CNS drug development can take place in the absence of any consideration of the blood-brain barrier. These contradictory beliefs are illustrated by recent reviews of drug development for AD [1202][1203][1204][1205], PD [755,1206], stroke [1207], brain cancer [1208], Huntington's disease [1209], ALS [1210], ataxia [1211], spinal cord injury [1212], traumatic brain injury [1213], or addiction [1214]. In none of these reviews on drug development for specific brain diseases was the BBB even mentioned, so the crucial issue of brain drug delivery was uniformly in absentia in the CNS drug development process.…”
Section: Perspectivementioning
confidence: 99%
“…Yet, CNS drug developers practice their craft by adhering to two conflicting beliefs: (a) drugs for CNS disease can be developed, and (b) CNS drug development can take place in the absence of any consideration of the blood-brain barrier. These contradictory beliefs are illustrated by recent reviews of drug development for AD [1202][1203][1204][1205], PD [755,1206], stroke [1207], brain cancer [1208], Huntington's disease [1209], ALS [1210], ataxia [1211], spinal cord injury [1212], traumatic brain injury [1213], or addiction [1214]. In none of these reviews on drug development for specific brain diseases was the BBB even mentioned, so the crucial issue of brain drug delivery was uniformly in absentia in the CNS drug development process.…”
Section: Perspectivementioning
confidence: 99%
“…In addition, α‐synuclein is a neuronal protein that regulates synaptic vesicle trafficking and neurotransmitter release. A clinical trial showed that treatments that use small molecule α‐synuclein aggregation therapy, monoclonal antibody, or gene therapy could be better than other clinical trials/therapies for the treatment in the future (Prasad & Hung, 2021). Moreover, a real‐life study revealed a continued reduction in motor fluctuations in patients who received 2 years of continuous treatment with apomorphine as an under‐the‐skin infusion (Meira et al., 2021).…”
Section: The Spot Of Parkinson's Diagnosis In the Genetic Eramentioning
confidence: 99%
“…Gene therapy is a rapidly growing market across the world with over 700 gene therapy clinical trials ongoing as of 2019, seeking to solve a variety of diseases and disorders, such as Parkinson's Disease, 1,2 Cystic Fibrosis 3,4 and various types of cancer 5,6 at the genomic level. Current clinical applications in gene therapy make use of adeno-associated viral vectors (AAVs) due to their unmatched gene delivery efficiency but limitations in max gene size, disputed safety, high cost of production and lack of ease in scalability has drawn the desire for an alternative for gene delivery applications.…”
Section: Overviewmentioning
confidence: 99%